Study on Transient Total Heat B-G Model of Air Supply in Large Space during Summer - Huang Chen; Zhu Jiyang; Yang Tong; Wang Fei; Zou Zhijun; Fan Qianhong; Miao Yufeng (Zhileng xuebao)
In this study, the harmonic method was introduced to solve the inner wall temperature problems of an envelope structure with heat storage characteristics in a large-space building with stratified air conditioning. The transient experimental results were used to calculate the heat storage of the indoor air. Combined with the diffusion characteristics of the indoor moisture, the transient full-heat six-zone Block-Gebhart (B-G) model was established under summer operating conditions. The results showed that the average absolute errors were between 0.44-1.12 ℃ and 0.63-1.96 ℃, in terms of the differences between the predicted and experimental values of the air and wall temperatures in the four regions above ground level, respectively, while the indoor air enthalpy was 1.85-1.96 kJ/kg. However, the errors in air and wall temperature, as well as the air enthalpy in the fifth and sixth zones close to the roof were higher and the predictions lower than the experimental results. The results showed that it was feasible to use the harmonic method and experimental results to analyze the transient solution of the thermal environment in large-space buildings.